2022
DOI: 10.5415/apallergy.2022.12.e31
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of IgE-mediated cow milk, egg, and peanut allergy in young Singapore children

Abstract: Background The rising prevalence of food allergy reported in the United States, UK, and Australia may be attributable to the rise in peanut allergy prevalence. The food allergy prevalence in other parts of the world such as Asia is, however, less well documented. Objective This study aimed to evaluate the prevalence of cow's milk, egg, and peanut allergies in a general population of Singaporean children below 30 months of age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…12 Several Singaporean studies identified peanuts as a common allergen. 13,14 In contrast, prior Singaporean studies identified no cases of peanut allergy, suggesting a change in dietary or other social patterns. 14,15 The patterns of food allergy in developing countries may elucidate the link between progressive urbanization and the development of food allergies; South African data suggested a fivefold discrepancy between rural and urban rates of food allergy.…”
Section: Ne W Trends In Food Allergy Pre Valen Cementioning
confidence: 87%
See 1 more Smart Citation
“…12 Several Singaporean studies identified peanuts as a common allergen. 13,14 In contrast, prior Singaporean studies identified no cases of peanut allergy, suggesting a change in dietary or other social patterns. 14,15 The patterns of food allergy in developing countries may elucidate the link between progressive urbanization and the development of food allergies; South African data suggested a fivefold discrepancy between rural and urban rates of food allergy.…”
Section: Ne W Trends In Food Allergy Pre Valen Cementioning
confidence: 87%
“…Surveys from China and India suggested 10‐fold differences in rates of IgE‐mediated allergy; 0.14% in India and 1.5% in Hong Kong 12 . Several Singaporean studies identified peanuts as a common allergen 13,14 . In contrast, prior Singaporean studies identified no cases of peanut allergy, suggesting a change in dietary or other social patterns 14,15 .…”
Section: New Trends In Food Allergy Prevalencementioning
confidence: 99%
“…In our study, egg was the top cause of food anaphylaxis in children 0-4 years, and in infants below 1 year, food anaphylaxis was mainly caused by eggs (50%) and milk (23.5%). We postulate that egg anaphylaxis was contributed by egg being the most prevalent food allergy in young Singaporean children [26] coupled with the traditional consumption of partially cooked egg such as steamed egg and egg-drop congee, possibly in a child unknown to have egg allergy. The anaphylaxis IR of children above 5 years rose then plateaued, possibly related to declining rates of egg anaphylaxis in older children in the later years.…”
Section: Discussionmentioning
confidence: 99%
“…Anaphylaxis visits were just consistently more common in children of other ethnicities and suggestive of a higher prevalence of food allergy in children of Caucasian, Japanese and mixed‐race descent. In a questionnaire survey of general population Singaporean children, the prevalence of the most common food allergy, egg, was only 1.4% [26]. In comparison, the prevalence of egg allergy was 9% based on food challenges in the Australian HealthNuts cohort [35] and 6% based on doctor certification of infant egg allergy in Japanese nurseries [36].…”
Section: Discussionmentioning
confidence: 99%